The Study on Biological PH Treatment of Acidic Palm Oil Mill Effluent - N., Zainol; Siti Mazlifah, Ismail (Penerbit Universiti Teknologi Malaysia, 2015)

(untitled)
This study investigated the biological pH treatment of acidic palm oil mill effluent (POME). In this study soil mixed culture (SMC) was acclimatized for 10 days (30°C and 150 rpm) with POME and used as inoculum. Selected factors used in this study were reaction time (3-5 days), temperature (25-30 °C), agitation speed (150-180 rpm), soil to water ratio (1:1 and 1:3) and inoculum types (peat and alluvium inoculum). Response surface method (RSM) was used to design and analyzed experimental data. In this study reaction time gave highest contribution which was at 29.81%. Reaction time was important for microbial growth in biological pH treatment. Interaction between reaction time and agitation speed gave highest contribution which was at 17.21%. Agitation provides a proper mixing on acidic POME and SMC thus increased the microbial activities. In this study, analysis of variance (ANOVA) was used to analyze the experimental data and the coefficient of determination (R2) value of 0.8301 was obtained. This study had proven the application of RSM was useful in experimental data analysis and increased the pH value from 4 to 8.